Organizational gender aspects : a baseline study of socio-economic effects of Northland Resources ore establishment in northern Sweden and Finland - Abrahamsson, Lena (Luleå tekniska universitet, Arbetsvetenskap, 2008)
Godkänd; 2008; 20090203 (biem)